Evaluation of Clinical & Etiological Profile of Children with Seizures - Jagannath H.N (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Seizures are a transient occurrence of signs and/or symptoms resulting from abnormal excessive or synchronous neuronal activity in the brain. Better understanding of seizures in terms of clinical presentation and etiology is required not only for abortion of acute attack but also for long term control of epilepsy.Subjects and Methods: This retrospective observational study included those children who were admitted with seizures within last 1 year time period of our study. Variables including age, sex, type of seizure, laboratory test results, neuroimaging, EEG findings, duration of hospital stay, diagnosis and final outcome were studied.Results: Incidence of seizures decreased with increasing age with less than 5 years age group most commonly involved. Generalized tonic clonic seizure were the most common type of seizure with febrile seizures being most common. etiology followed by CNS infections. Febrile seizures had best outcome while CNS infections had highest morbidity and mortality.Conclusion: We found CNS infections to be the most common etiology and a poor outcome. Acute episode of seizures is one of the commonest causes of hospitalization with high morbidity and mortality. Being a developing nation, strict measures to prevent infection can reduce the occurrence of seizures in children thus preventing long term neurological sequelae in children.